2001
DOI: 10.1046/j.0306-5251.2001.01417.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of β‐adrenoceptor antagonists on the pharmacokinetics of rizatriptan, a 5‐HT1B/1D agonist: differential effects of propranolol, nadolol and metoprolol

Abstract: Aims Patients with migraine may receive the 5-HT 1B/1D agonist, rizatriptan (5 or 10 mg), to control acute attacks. Patients with frequent attacks may also receive propranolol or other b-adrenoceptor antagonists for migraine prophylaxis. The present studies investigated the potential for pharmacokinetic or pharmacodynamic interaction between b-adrenoceptor blockers and rizatriptan.Methods Four double-blind, placebo-controlled, randomized crossover investigations were performed in a total of 51 healthy subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 16 publications
(19 reference statements)
0
20
0
Order By: Relevance
“…Rizatriptan is mainly metabolized by MAO-A via oxidative deamination [525]. Propranolol, but not metoprolol and nadolol, increased its AUC by 70% through MAO-A inhibition [526]. In vitro studies showed that propranolol, but not metoprolol and nadolol, significantly inhibited the production of the indole-acetic acid metabolite of rizatriptan and sumatriptan.…”
Section: Anti-migraine Drugsmentioning
confidence: 98%
“…Rizatriptan is mainly metabolized by MAO-A via oxidative deamination [525]. Propranolol, but not metoprolol and nadolol, increased its AUC by 70% through MAO-A inhibition [526]. In vitro studies showed that propranolol, but not metoprolol and nadolol, significantly inhibited the production of the indole-acetic acid metabolite of rizatriptan and sumatriptan.…”
Section: Anti-migraine Drugsmentioning
confidence: 98%
“…Having multiple routes for metabolism is an advantage since there are alternative metabolic pathways with in-built redundancy, so if one pathway is non-functional, others can take over to ensure the effectiveness of the drug as well as avoiding drug accumulation (and therefore adverse events) by fast production of inactive metabolites. Drugs with single dominant metabolic pathways are also more likely to interact with other drugs metabolised by the same pathway, as seen in the case of the necessity of lowering the dose of rizatriptan in migraine patients also receiving preventive treatment with propranolol [Goldberg et al, 2001].…”
Section: Triptan Metabolic Profilingmentioning
confidence: 98%
“…Inhibition of rizatriptan metabolism since both drugs are metabolized by MAO-A and compete with each other Dose of rizatriptan should be reduced to 5 mg; maximum 15 mg/day [127] Rizatriptan, zolmitriptan, sumatriptan/MAO inhibitors Increased risk of triptan adverse reactions…”
Section: Risk Of Serotoninergic Syndromementioning
confidence: 99%